Benefits of Binahong Leaves for Health: Natural Solutions for Various Diseases - Tedjo Narko; Sudiyarti Sudiyarti; Zaenal Zaenal; Fitri Ardiani (PT. Anagata Sembagi Education, 2025)
This study aims to explore the benefits of binahong leaves (Anredera cordifolia) as a natural solution for various diseases. The method used is a literature review by collecting and analyzing scientific sources, such as indexed journals, reference books, and research reports from academic and health institutions. The analysis focused on the content of active compounds, mechanisms of action, and the effectiveness of binahong leaves based on laboratory tests and clinical studies. The results showed that binahong leaves contain flavonoids, saponins, and alkaloids that have antioxidant, anti-inflammatory, and antibacterial effects. The benefits include accelerating wound healing, lowering blood pressure, and potential therapy for diabetes and cancer. Its use in traditional medicine has long been proven, both in the form of decoctions, juices, and external medicines. Although its effectiveness is supported by various studies, further studies are needed to ensure safety and proper dosage, especially for long-term use. With increasing awareness of natural medicine, binahong leaves have great potential as an alternative in the medical world. The development of binahong-based products can expand its use as a complementary therapy that supports conventional medicine.